Voices From the Classroom: Students’ Perceptions of CEFR-Based English Materials in an Islamic Higher Education Context - Haris Munandar; Faiz Rizki Muhammad; Dinar Dipta (Universitas PGRI Madiun, 2026)
This study aimed to investigate students’ views toward English classroom materials used in the Language Class Program (LCP) at Universitas Darussalam Gontor. It also examined the process of selecting English teaching materials implemented in the program. This research employed a qualitative descriptive approach involving twenty freshmen students as participants. The data were collected through semi-structured interviews, classroom observations, and document analysis, and were analyzed using thematic analysis. The findings revealed that the process of selecting English materials in the LCP was primarily based on international standards, particularly the Common European Framework of Reference (CEFR), and relied on materials adapted from the British Council. The material selection focused on students’ academic needs, language proficiency levels, and the development of four language skills, with greater emphasis on speaking and listening skills. However, some materials were considered less suitable for pesantren context and required further adaptation by the tutors. Furthermore, the study identified four main themes regarding students’ perceptions of the English materials: understanding of the materials, material suitability, skill difficulty, and students’ motivation in learning using the materials. Overall, students perceived the materials as relevant and useful for their academic needs, although differences were found in levels of comprehension, difficulties in certain language skills, particularly listening and writing, and fluctuating learning motivation. Therefore, this study suggests that English teaching materials should be continuously developed and adapted to better suit students’ needs and the educational context of the institution.